1988
DOI: 10.1111/j.1432-1033.1988.tb14041.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of influenza virus with gangliosides and liposomes containing gangliosides

Abstract: It has already been shown that influenza virus binds unspecifically to liposomes containing ganglioside GM1 whereas with gangliosides G D l b and G,,, binding occurs in a specific and saturable manner [Slepushkin et al. (1986) Biol. Membr. 3,229 -2351. In the present study the mode of interaction between influenza virus and various gangliosides or phospholipid liposomes containing cholesterol and gangliosides has been investigated.The influence of exogenous gangliosides on the structure of the viral envelope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Upon photolysis, these photoactivatable lipids generate highly reactive nitrene radicals which covalently bind to protein sites that are in contact with the probe. Thus, one can identify changes in the relative position of hydrophobic protein segments and surrounding lipids (21,22). Recently a photoactivatable analog of phosphatidylethanolamine labeled in the polar head group moiety was shown to cross-link efficiently to apolipoprotein B (apo-B) of LDL and to apo-A 1 of HDL (23).…”
Section: Methodsmentioning
confidence: 99%
“…Upon photolysis, these photoactivatable lipids generate highly reactive nitrene radicals which covalently bind to protein sites that are in contact with the probe. Thus, one can identify changes in the relative position of hydrophobic protein segments and surrounding lipids (21,22). Recently a photoactivatable analog of phosphatidylethanolamine labeled in the polar head group moiety was shown to cross-link efficiently to apolipoprotein B (apo-B) of LDL and to apo-A 1 of HDL (23).…”
Section: Methodsmentioning
confidence: 99%
“…All compositions included 5% fluorescent lipid probe and, if not stated otherwise, 5% disialoganglioside, which serves as a receptor for HA binding [33]. DSPC/cholesterol liposomes (DSPC-LS) had the following composition: 49.5% DSPC, 40.5% cholesterol, 5% RhDPPE, and 5% disialoganglioside.…”
Section: Liposomesmentioning
confidence: 99%
“…As gangliosides are able to bind influenza virus particles to the surface of ceils (Bergelson et al, 1982) or liposomes (Slepushkin et al, 1988) they may be expected to compete with natural receptors inhibiting virus adsorption on the cell surface. To test this possiblity, the virus was pretreated with GM1 for 1 h at 37 °C and the mixture then was injected intranasally into mice of the susceptible line (CBA).…”
Section: Effect Of Virus Pretreatment With Gangliosides On Infectionmentioning
confidence: 99%
“…It was demonstrated that this effect of gangliosides GTlb or Golb was due to their specific interaction with virus haemagglutinin (HA) which induces a rearrangement of the viral lipids resulting in the bilayer areas of the viral envelope becoming fluid to a significant degree. This in turn promotes fusion of the virus with target membranes (Slepushkin et al, 1988). Gangliosides of other types, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation